Effectiveness of Resilience Lecture Performance Program among Male Adolescents in Region 2 Juvenile Vocational Training Center, Ratchaburi Province, Thailand - Chaidej, Pichkrai; Viwatpanich, Kanvee (Journal of Health Science of Thailand, 2024)
A quasi-experiment with a single-group pretest-posttest design, conducted in Regional 2 juvenile vocational training center, Ratchuburi Province, Thailand, aimed to evaluate the effectiveness of the Resilience Lecture Performance Program (RLPP). A total of fifty adolescents were voluntarily registered and enrolled. The RLPP was developed by the researchers and consisted of four twelve-hour modules. The research revealed a statistically significant improvement in post-test resilience scores (Mean 77.22±8.10) compared to pretest scores (Mean 70.85±7.73), measured by the Resilience Rating 3 Scale (RS-48). Following the intervention’s implementation, a statistically significant improvement was observed in social skills, problem-solving abilities, and meaning and purpose. Additionally, there was an increase in self-autonomy, but this gain did not reach statistical significance. The program reduced the low level from 13.04% to 4.35% and decreased the intermediate level from 86.96% to 71.74%. Simultaneously, RLPP exhibited a notable enhancement in resilience, progressing from a pretest score of zero to a posttest score of 23.91%.